2023
DOI: 10.3390/molecules28217340
|View full text |Cite
|
Sign up to set email alerts
|

Atractylone in the Atractylodes macrocephala Rhizoma Essential Oil and Its Anti-Inflammatory Activity

Ling Li,
Yihao He,
Nan Wang
et al.

Abstract: The aim of this study was to conduct a screening of potential therapeutic compounds found in the Atractylodes macrocephala rhizoma essential oil (AO) and explore its mechanism of action in the treatment of ulcerative colitis (UC). An inflammation cell model was employed in conjunction with phospho-antibody array technology to explore potential therapeutic compounds of AO and their anti-inflammatory and antioxidant effects. Furthermore, we assessed their efficacy and mechanisms of action in treating dextran sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Tang T J et al [20] reported that glycyrrhizin can promote AMPK phosphorylation and SIRT1 protein expression and inhibit the phosphorylation of nuclear factor NF-κB p65 to protect H9c2 cells from H 2 O 2 -induced cell damage. Li L et al [21] reported that Atractylodes inhibited the expression of pro-inflammatory cytokines such as IL-6 and TNF-α and down-regulated the PI3K-AKT signaling pathway, thereby helping to enhance the repair of intestinal epithelial barrier function and alleviate colon damage in mouse colitis models. Shi K et al [22] reported that Atractylodes lancea rhizome attenuates oxidative stress and inflammation through the TLR4/NF-κB and Keap1/Nrf2 signaling pathways, thereby alleviating LPS-induced acute lung injury.…”
Section: Introductionmentioning
confidence: 99%
“…Tang T J et al [20] reported that glycyrrhizin can promote AMPK phosphorylation and SIRT1 protein expression and inhibit the phosphorylation of nuclear factor NF-κB p65 to protect H9c2 cells from H 2 O 2 -induced cell damage. Li L et al [21] reported that Atractylodes inhibited the expression of pro-inflammatory cytokines such as IL-6 and TNF-α and down-regulated the PI3K-AKT signaling pathway, thereby helping to enhance the repair of intestinal epithelial barrier function and alleviate colon damage in mouse colitis models. Shi K et al [22] reported that Atractylodes lancea rhizome attenuates oxidative stress and inflammation through the TLR4/NF-κB and Keap1/Nrf2 signaling pathways, thereby alleviating LPS-induced acute lung injury.…”
Section: Introductionmentioning
confidence: 99%